Simulation-based semi-empirical comparative study of fixed and vectored thruster configurations for an underwater vehicle. (15th August 2021) - Kadiyam, Jagadeesh; Mohan, Santhakumar; Deshmukh, Devendra; Seo, Taewon
Abstract: In the recent past, intervention-class autonomous underwater vehicles (AUVs) have gained the ocean/marine research community's attention due to their multidisciplinary operational capabilities. This article discusses a detailed comparative-performance study of an underwater vehicle (UV) with two different actuator configurations based on fixed-thrusters and vectored thrusters. The fixed-thruster configuration consists of eight thrusters. Four thrusters generate thrust in the horizontal plane and the remaining thrusters produce thrust in heave direction. The vectored thruster configuration has four thrusters placed at diagonal corners of a rectangular vehicle, and four independent internal servomotors rotate these thrusters. The classification terminology in this article identifies the underwater vehicle without vectoring capability as Fixed-Thruster Underwater Vehicle (FTUV) and the one with vectoring capability as Vectored-Thruster Underwater Vehicle (VTUV). Furthermore, a nonlinear controller is designed, based on a backstepping scheme for tracking a given spatial profile in a three-dimensional space. An underwater robot's control for a trajectory tracking problem is useful for any real-time multidisciplinary autonomous applications. The comparative simulation results are summarized to validate both the vehicle variants' performance differences. Highlights: Performance investigations of an underwater vehicle with fixed and vectored thrusters. Modular vehicle design helps to implement two propulsion strategies in the same vehicle. A detailed thruster model is implemented in both the variants by using empirical data. Study the feasibility of vectored thrusters towards high manoeuvrability demanding applications. Actuator constraints, thruster/hull interaction, and ocean currents are simulated.